PENGEMBANGAN E-MODUL BIOLOGI BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA - Selvina Dima Sinta (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2023)
This study plans to: (1) produce issue based learning (PBL) science e-modules to further develop understudy self-directed learning, (2) decide the use of PBL-based science e-modules to further develop understudy self-controlled learning, (3) decide the impact of PBL-based science e-module to work on understudies' self-managed learning. Using a four-dimensional model, this study is an R&D (research and development) study: characterize, plan, create, and scatter. PBL-based biology e-modules, learning response questionnaires, and student self-regulated learning questionnaires served as the research instruments. The average percentage score obtained by expert validators and small-scale student trials demonstrate the e-module's viability. The use of the e-module should be visible from the typical score acquired in the learning reaction survey. The acquisition of self-regulated learning questionnaires for early and late students reveals the influence of e-modules on student self-regulation. Using a straightforward linear regression test, to determine how the e-module affected the self-regulated learning of students. The findings revealed: 1) PBL-based science e-module to further develop understudies' self-controlled learning is possible to use with a score of 83% master approval in the